1995
DOI: 10.1159/000098682
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Neuropathic Pain

Abstract: Paresthesia-producing (PP), but not periventricular grey (PVG) deep brain stimulation (DBS) proved effective in steady neuropathic pain in 25 patients receiving both, regardless of the PP site stimulated, but PVG-DBS suppressed allodynia or hyperpathia in 3 cases of stroke-induced pain. In patients with stroke-induced central pain, PP-DBS was unpleasant in 6 of 17 (35%), all with allodynia and/or hyperpathia, but not in patients with spinal cord central or peripheral neuropathic pain with allodynia or hyperpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 0 publications
0
33
0
5
Order By: Relevance
“…In the following decades, electrical stimulation of the thalamus, internal capsule, and periaqueductal gray matter or periventricular gray matter (PVG) became commonly used procedures to treat chronic refractory pain. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Within the last decade, the number of patients with chronic pain treated with DBS, as well as the number of the published studies, have progressively decreased, mainly because of the lack of solid scientific evidence of DBS safety and efficacy and the development of less invasive alternatives to manage nociceptive pain. Although DBS produced impressive results in a subset of patients, the results were highly variable, and appropriate patient selection seems to be very important.…”
mentioning
confidence: 99%
“…In the following decades, electrical stimulation of the thalamus, internal capsule, and periaqueductal gray matter or periventricular gray matter (PVG) became commonly used procedures to treat chronic refractory pain. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Within the last decade, the number of patients with chronic pain treated with DBS, as well as the number of the published studies, have progressively decreased, mainly because of the lack of solid scientific evidence of DBS safety and efficacy and the development of less invasive alternatives to manage nociceptive pain. Although DBS produced impressive results in a subset of patients, the results were highly variable, and appropriate patient selection seems to be very important.…”
mentioning
confidence: 99%
“…DBS for chronic pain has been undertaken for over half a century [15,16,17,18,19,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41], its use preceding the ‘gate theory' by a decade. However, multiple reports had conveyed an overall impression regarding DBS for pain that had led most neurosurgeons to abandon the technique [15,41].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study reporting satisfactory results occurred in 1995, when Tasker and Vilela Filho [7] achieved success in 3 out of 6 patients with implantations in “parasthesia-producing” sites which consisted of somatosensory areas. In 2006 a trial was conducted in 11 DRS patients with both PVG and VPL electrodes, and this was the largest cohort since 1987 [59].…”
Section: Methodsmentioning
confidence: 99%
“…Accounting for the 7 patients who achieved no pain relief brings the average reduction closer to 26%. Tasker and Vilela Filho [7] found that a trial of PAG/PVG stimulation did not produce pain relief in DRS patients, and in fact it evoked unpleasant effects in nearly all of the patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation